Customer Engagement in Emerging Markets: Framework and Propositions - Hollebeek, Linda D.; Muniz-Martinez, Norberto; Clark, Moira; Simanaviciute , Agne; Letukyte , Neda (Organizations and Markets in Emerging Economies, 2022)
Emerging markets are a major contributor to global GDP, thus offering a primary source for economic growth. However, despite these acclaimed benefits, little remains known regarding customer engagement (i.e., a customer’s resource investment in his/her brand interactions) in emerging markets, thus exposing a pertinent literature-based gap. The development of enhanced insight into customer engagement dynamics in emerging (vs. developed) markets is important, given the idiosyncrasies characterizing these markets (e.g., chronic resource shortages, inadequate infrastructure), thus warranting the undertaking of further research in this integrative area. In response to this gap, this paper develops a framework and an associated set of Propositions of emerging market-based customer engagement, by drawing on Sheth’s (2011) emerging market hallmarks. Specifically, our Propositions postulate that the emerging market tenets of socio-political governance, inadequate infrastructure, market heterogeneity, chronic resource shortages, and unbranded competition uniquely affect emerging market-based customer engagement. We conclude by discussing our findings and by outlining key implications that arise from our analyses.
Keywords: customer engagement; emerging markets; framework; propositions